Une nouvelle traduction signifie-t-elle un nouveau livre ? La Salle de bain retraduite en Italien par Roberto Ferrucci - Thea Rimini (MediAzioni)
This article compares Leonella Prato Caruso’s first Italian translation of Jean-Philippe Toussaint’s La Salle de bain (Guanda, 1986) with Roberto Ferrucci’s re-translation (Amos, 2021). Why did Ferrucci, Toussaint’s regular translator since 2001, feel the urgent need to re-translate La Salle de bain for the small publishing house Amos? What differences ‒lexical, syntactical, and stylistic‒ emerge from a comparative analysis of the first and second translations against the original text? Can we say that a new translation is in fact a new book? After analysing the “contextual” and “textual voices” (Alvstad, Assis Rosa 2015), the construction of the paratext and the contrastive analysis of certain passages revealing significant syntactic and lexical differences between the first and second translations, it is possible to affirm that the new version of La Salle de bain, produced by a “Toussaintian” translator such as Ferrucci, is truly a new Stanza da bagno.